Vibration therapy role in neurological diseases rehabilitation: an umbrella review of systematic reviews - Moggio, Lucrezia; de Sire, Alessandro; Marotta, Nicola; Demeco, Andrea; Ammendolia, Antonio (Disability and rehabilitation, 2022)
To summarize the findings and evaluate the role of vibratory therapy in the rehabilitation of neurological diseases. We systematically research PubMed, Scopus, Embase, Physiotherapy Evidence Database (PEDro), Web of Science, and Cochrane library databases from the inception until November 2020. We included studies that compared whole-body vibration (WBV) or focal muscle vibration (FMV) with placebo, sham, or another form of exercise in neurological disease rehabilitation in children and adults that result in motor impairments and disability. We included 16 systematic reviews with good methodological quality evaluated using the Joanna Briggs Institute Umbrella Review Assessment and Review of Information appraisal tool. In stroke patients, WBV appears to play a role in improving gait and balance, while FMV is more effective in reducing spasticity. In multiple sclerosis and cerebral palsy, no evidence suggested that vibration therapy increases some patient outcomes. WBV and FMV appear to play a considerable role in reducing spasticity and improving gait, balance, and motor function in stroke patients. By contrast, vibration therapy seems to be unable to reduce spasticity in multiple sclerosis and cerebral palsy. Also, correct use parameters for this therapy could not be defined. IMPLICATIONS FOR REHABILITATION Based on the growing number of systematic reviews, this umbrella review aimed to summarize the findings and evaluate the role of vibration therapy in the rehabilitation of neurological diseases. Whole-body vibration and focal muscle vibration appear to play a considerable role in reducing spasticity and improving gait, balance, and motor function in patients affected by stroke. Focal muscle vibration appears to be more useful if applied to non-spastic antagonist muscles with reciprocal inhibitory action on spastic muscles in subjects affected by stroke. Vibration therapy seems not to be able to reduce spasticity in multiple sclerosis and cerebral palsy.